If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + y)(4x + -5y) = 0 Multiply (x + y) * (4x + -5y) (x(4x + -5y) + y(4x + -5y)) = 0 ((4x * x + -5y * x) + y(4x + -5y)) = 0 Reorder the terms: ((-5xy + 4x2) + y(4x + -5y)) = 0 ((-5xy + 4x2) + y(4x + -5y)) = 0 (-5xy + 4x2 + (4x * y + -5y * y)) = 0 (-5xy + 4x2 + (4xy + -5y2)) = 0 Reorder the terms: (-5xy + 4xy + 4x2 + -5y2) = 0 Combine like terms: -5xy + 4xy = -1xy (-1xy + 4x2 + -5y2) = 0 Solving -1xy + 4x2 + -5y2 = 0 Solving for variable 'x'. Factor a trinomial. (4x + -5y)(x + y) = 0Subproblem 1
Set the factor '(4x + -5y)' equal to zero and attempt to solve: Simplifying 4x + -5y = 0 Solving 4x + -5y = 0 Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 4x + -5y + 5y = 0 + 5y Combine like terms: -5y + 5y = 0 4x + 0 = 0 + 5y 4x = 0 + 5y Remove the zero: 4x = 5y Divide each side by '4'. x = 1.25y Simplifying x = 1.25ySubproblem 2
Set the factor '(x + y)' equal to zero and attempt to solve: Simplifying x + y = 0 Solving x + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. x + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 x + 0 = 0 + -1y x = 0 + -1y Remove the zero: x = -1y Simplifying x = -1ySolution
x = {1.25y, -1y}
| f(x)=4000x^2 | | (x+y)(x-7y)=0 | | 3c-2=10-c | | 2(x+10)=2(3x-8) | | (s-3t)(s-2t)=0 | | x=12(24-6y) | | 5x=100+4y | | f(x-2)=2x+5 | | 12v^7/54v^4 | | 2*54=u | | h-4.9=13.9 | | 85*5=w | | 4w+1=9w-18 | | -3a+1=2a+11 | | 8k+1=180 | | 20k+11=180 | | 5w^6/45w^4 | | 4x^2-39=4x | | 2/3x-1/6=5/x-2/3 | | 2x-(3x-3)=3x-5 | | 3H+2C=5.45 | | x(x+3)=11 | | 9-4m=2m-3 | | Y=2(0+3)(0-4) | | 4y-23=10+y | | 23+13x-15+5x-27x= | | 14000V=-2000t+20000 | | 5(9a)= | | 14000V=-2000+20000 | | -10x+14-8x+9= | | 3x-4(1-2x)=2x-(x+1) | | 2(a-b)= |